An evaluation of the integration of oral pre-exposure prophylaxis (prep) as standard of care for HIV prevention in clinical trials in South Africa - Beesham, Ivana (University of the Witwatersrand, Johannesburg, 2023)
Background: Oral tenofovir-based pre-exposure prophylaxis (PrEP) is an effective biomedical HIV prevention option. In 2015, the World Health Organization (WHO) recommended oral PrEP for those at substantial risk of HIV infection, and several countries have since adopted oral PrEP into their national guidelines. In the context of trials, HIV endpoint-driven trials frequently enrol individuals who are at elevated risk of acquiring HIV. Ethical guidelines recommend that study sponsors and investigators should provide access to a package of HIV prevention methods to trial participants, as recommended by WHO, including adding new prevention methods as these are validated. In 2017, the South African Medical Research Council recommended that oral PrEP be provided in HIV prevention trials. The Evidence for Contraceptive Options and HIV Outcomes (ECHO) Trial was ongoing at the time and incorporated oral PrEP into the trial’s HIV prevention package, including the onsite provision of oral PrEP at the South African trial sites during the last eight months of the trial. The ECHO Trial, conducted from 2015 to 2018, enrolled women aged 16-35 years, from 12 research sites in four African countries, and assessed the effect of three contraceptives on HIV incidence. In 2019, when this PhD project was conceptualised, there was a lack of data on the integration of oral PrEP as part of the HIV prevention package in HIV endpoint-driven trials. To address this gap, I evaluated the integration of oral PrEP as standard of care for HIV prevention in clinical trials in South Africa. Objectives: 1. To describe the process of implementing oral PrEP provision, the uptake of oral PrEP and the characteristics of women who initiated (versus those who did not initiate) oral PrEP during the ECHO Trial. 2. To evaluate oral PrEP adherence and factors associated with adherence by conducting plasma tenofovir (TFV) drug level testing using stored blood samples among a subset of women from South Africa who reported current oral PrEP use at the final ECHO Trial visit. 3. To describe the experiences of women who initiated oral PrEP at the Durban, South Africa, ECHO Trial site. 4. To explore post-trial access to oral PrEP, and barriers and enablers to post-trial oral PrEP access, among a subset of women from the Durban, South Africa, ECHO Trial site. 5. To review the current status of oral PrEP as standard of care for HIV prevention in clinical trials in South Africa. Methods: This was a mixed methodology study, conducted from 2019 to 2022, and both qualitative and quantitative methods were utilized. I describe the process undertaken by the ECHO Trial team to incorporate oral PrEP delivery into the trial’s HIV prevention package, including the onsite provision of oral PrEP by ECHO Trial staff at the South African trial sites. Characteristics between women who ever initiated oral PrEP versus those who had access to but did not initiate oral PrEP, were assessed using Chi-squared/Fisher’s exact tests for categorical variables and t-tests for continuous variables. HIV seroincidence comparisons between participants who never versus ever initiated oral PrEP were modelled using exact Poisson regression. To objectively measure adherence to oral PrEP, plasma samples collected at the final ECHO Trial visit, from a subset of women enrolled at the South African ECHO Trial sites, who reported ongoing PrEP use, were tested for TFV. Bivariate logistical regression was used to evaluate participant characteristics associated with quantifiable TFV at the final ECHO Trial visit. 10 | P a g e To understand experiences of women who used oral PrEP and patterns of oral PrEP use, we conducted questionnaires with women who initiated oral PrEP onsite at the Durban, South Africa, ECHO Trial site. Face-to-face questionnaires were conducted approximately three months following oral PrEP initiation, and explored reasons for using and discontinuing oral PrEP, side effects experienced, oral PrEP adherence and disclosure of oral PrEP use. I also evaluated factors associated with oral PrEP continuation at the final ECHO Trial visit using univariate and multivariate logistical regression. Among women continuing oral PrEP at ECHO Trial exit, telephonic follow-up was conducted 4-6 months later, to briefly explore oral PrEP access and ongoing use following study exit. Additional face-to-face, participant in-depth interviews were conducted in 2021 with a subset of women from the Durban, South Africa, ECHO Trial site, who reported ongoing oral PrEP use at ECHO Trial exit and who were given a 3-month PrEP supply at study exit. The interviews explored barriers and enablers to post-trial oral PrEP access. Finally, telephonic in-depth interviews were held with key stakeholders from research sites across South Africa known to conduct HIV endpoint-driven clinical trials to explore their perspectives on providing oral PrEP as HIV prevention standard of care in clinical trials in South Africa. Participant and stakeholder interviews were audio-recorded and transcribed, and thematic analysis was facilitated using NVivo. Results: Our key findings indicate that it was feasible to integrate oral PrEP as standard of care for HIV prevention in the ECHO Trial. PrEP uptake was 17.2% (622/3626) among those eligible for oral PrEP when it became available. Women who initiated oral PrEP were more likely to be unmarried, not living with their partner, having multiple partners; and less likely to be earning their own income and receiving financial support from partners (all p<0.05). There were 37 HIV seroconversions among women who had access to oral PrEP but did not initiate oral PrEP, and 2 seroconversions among women who initiated oral PrEP (HIV incidence 2.4 versus 1.0 per 100 person-years; Incidence Risk Ratio = 0.35; 95% confidence interval (CI) = 0.04 to 1.38). Among the 260 plasma samples from the eight South African ECHO Trial sites that were available for TFV testing, plasma TFV was quantified in 36% of samples (94/260). Women >24 years old had twice the odds of having TFV quantified compared to younger women (Odds Ratio (OR) = 2.12; 95% CI = 1.27 to 3.56). Women who reported inconsistent/no use of condoms had lower odds of TFV quantification (age-adjusted OR = 0.47; 95% CI = 0.26 to 0.83). The ancillary study conducted at the Durban, South Africa ECHO Trial site found that onsite oral PrEP uptake was high (43%, 138/324). Almost all women who initiated oral PrEP at the trial site agreed to participate in the ancillary study (96%, 132/138). Of these, 88% reported feeling at risk of acquiring HIV. Most women (>90%) heard of oral PrEP for the first time from trial staff. Oral PrEP continuation via self- report was 87% at month-1, 80% at month-3, and 75% elected to continue using oral PrEP at trial exit and were referred to off-site facilities for ongoing access. Disclosure of oral PrEP use was associated with five-fold increased odds of continuing oral PrEP at trial exit (adjusted OR = 4.98; 95% CI = 1.45 to 17.13; p=0.01). At telephonic follow-up 4-6 months after women exited the ECHO Trial, >50% reported discontinuing PrEP. Qualitative interviews conducted with a subset of women from the Durban, South Africa ECHO Trial site identified several barriers to post-trial oral PrEP access at facilities such as long queues, facilities being located far from women’s homes, unsuitable clinic operating hours, negative attitudes from providers, and oral PrEP being unavailable at some clinics. Interviews with key stakeholders from research sites in South Africa found that most stakeholders reported incorporating oral PrEP provision as part of the HIV prevention package offered to participants in HIV endpoint-driven trials. Stakeholders identified barriers to oral PrEP 11 | P a g e uptake, adherence, persistence, and post-trial access. Demand creation, and education and counselling about oral PrEP were reported as factors that facilitated uptake. Conclusion: The ECHO Trial provides evidence that it was feasible to successfully integrate oral PrEP provision as part of the trial’s HIV prevention package offered to study participants. Other HIV endpoint-driven trials can utilize our findings as a model to integrate oral PrEP provision into the HIV prevention package offered in a trial. The ancillary study findings on PrEP uptake, adherence and persistence can be utilized to guide oral PrEP trials and implementation programs. While post-trial oral PrEP access was concerning and several barriers were identified, it is possible that with the scale-up of oral PrEP in the public sector in South Africa after the ECHO Trial was completed, participants exiting trials and desiring to continue oral PrEP could have better access
A Thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa, 2023
Keywords: HIV prevention; oral pre-exposure prophylaxis; standard of prevention; clinical trials; SDG-3: Good health and well-being